Determinisme Teknologi dalam Teknologi Komunikasi dan Informasi - Ratmanto, Teguh (FIkom Unisba, 2005)
Technological determinism, as the result of technology innovation, raised a constant debate among scholars concerning its position toward the society: whether it was caused by the society, or the effect of social change. This debate, in the end, produced two kinds of party: those who support technology, and those who against it, both the optimists or the pessimist one. Those who against technology believed that technology in no other way was created by society. The supporter, reversely, strongly believed that technology shaped society, even determine the future. Both party believed there is interplay between technology and society.